STRATEGI PPKBD (PEMBANTU PEMBINA KELUARGA BERENCANA DESA) DALAM SOSIALISASI METODE OPERASI WANITA (MOW) DI DESA SIRNABAYA KECAMATAN TELUKJAMBE TIMUR KABUPATEN KARAWANG - Kismanto, Adhwa Cahyani; Hoerniasih, Nia; Muis, Abdul (Comm-Edu (Community Education Journal), 2025)
This research aims to describe the strategies implemented by PPKBD (Village Family Planning Assistants) in disseminating the Female Sterilization Method (Metode Operasi Wanita/MOW) in Sirnabaya Village, Telukjambe Timur Subdistrict, Karawang Regency. The study employs a descriptive qualitative approach with data collection techniques including observation, unstructured interviews, and documentation. Informants were selected using purposive sampling, complemented by snowball sampling to identify other relevant sources. The findings reveal that the strategies used by PPKBD include personal, educational, participatory, and collaborative approaches involving local health institutions. Supporting factors for successful dissemination include PPKBD’s emotional closeness to the community and support from PLKB and community leaders. Barriers encountered involve low public awareness, misinformation, and limited resources. The study concludes that effective strategy and communication are key to increasing community participation in the MOW program.